2012
DOI: 10.1103/physreva.86.023841
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort pulses and short-pulse equations in 2+1 dimensions

Abstract: In this paper, we derive and study two versions of the short pulse equation (SPE) in (2 + 1) dimensions. Using Maxwell's equations as a starting point, and suitable Kramers-Kronig formulas for the permittivity and permeability of the medium, which are relevant, e.g., to left-handed metamaterials and dielectric slab wave guides, we employ a multiple scales technique to obtain the relevant models. General properties of the resulting (2 + 1)-dimensional SPEs, including fundamental conservation laws, as well as th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…Finally, it would also be of particular interest to extend our considerations to higher‐dimensional settings (e.g., Reference for a recent work related to the SPE model) and study – apart from solitons – other physically relevant and important phenomena, like collapse, vortex formation and their dissipative dynamics, and so on.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Finally, it would also be of particular interest to extend our considerations to higher‐dimensional settings (e.g., Reference for a recent work related to the SPE model) and study – apart from solitons – other physically relevant and important phenomena, like collapse, vortex formation and their dissipative dynamics, and so on.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[22], in which φ is a solution of the SG equation, and this idea is used to get periodic solutions of the SP equation [23] and the multisoliton solutions of the multi-component SP equation [24]. There exist several extensions of the SP equation including the discrete SP equation [6], the two-component SP [7,34], multi-component SP [24], stochastic SP [18], (2+1)-dimensional SP [31], complex SP [8,21], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The SPE was later used in the study of localized structures in frequency band gaps of nonlinear metamaterials [30]. Recently, two different versions of the SPE in (2 + 1) dimensions were studied in detail [31] and it was shown that ultrashort one-dimensional breathers appear to be fairly robust in the two-dimensional setting, while rather general two-dimensional localized initial conditions are transformed into quasi-one-dimensional dispersing wave forms, which are reminiscent of the one-dimensional solitons.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear effects associated with the spatiotemporal propagation of few-cycle optical pulses in nonlinear dispersive media, including nonlinearity-induced self-phase modulation, generation of higher harmonics, and the effects of diffraction, were analyzed in detail [46]. A detailed study of ultrashort pulses and short-pulse equations in (2 + 1) dimensions was also performed in a recent work by Shen et al [31]. Two versions of the short pulse equation in (2 + 1) dimensions were derived and by using Maxwell's equations as a starting point, and suitable Kramers-Kronig formulas for the permittivity and permeability of the medium, which are relevant, e.g., to left-handed metamaterials and dielectric slab waveguides, a multiple scales technique to obtain the relevant models was employed [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation